2021
DOI: 10.15252/emmm.202013249
|View full text |Cite
|
Sign up to set email alerts
|

Deletions in CWH43 cause idiopathic normal pressure hydrocephalus

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is a neurological disorder that occurs in about 1% of individuals over age 60 and is characterized by enlarged cerebral ventricles, gait difficulty, incontinence, and cognitive decline. The cause and pathophysiology of iNPH are largely unknown. We performed whole exome sequencing of DNA obtained from 53 unrelated iNPH patients. Two recurrent heterozygous loss of function deletions in CWH43 were observed in 15% of iNPH patients and were significantly enriched 6.6‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…We previously reported that mice harboring iNPH-associated deletions in CWH43 develop communicating hydrocephalus ( Fig. 1 A ) ( 7 ). To determine whether alterations in L1CAM may contribute to this phenomenon, we examined L1CAM immunoreactivity in the ventricular and subventricular zone of the mouse brain using an antibody directed against the C terminus of L1CAM.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…We previously reported that mice harboring iNPH-associated deletions in CWH43 develop communicating hydrocephalus ( Fig. 1 A ) ( 7 ). To determine whether alterations in L1CAM may contribute to this phenomenon, we examined L1CAM immunoreactivity in the ventricular and subventricular zone of the mouse brain using an antibody directed against the C terminus of L1CAM.…”
Section: Resultsmentioning
confidence: 93%
“…All experiments and procedures involving mice were approved by the University of Massachusetts Medical School Institutional Animal Care and Use Committee. C57bl6 mice harboring a Met533Ter mutation (coinciding to the human CWH43 deletion 4:49034669 CA/C; Leu533Ter) were generated using a CRISPR/Cas9 approach and bred to generate homozygous ( CWH43 M533/M533 ) animals as described previously ( 7 ). This mutation generates a stop codon that truncates the encoded Cwh43 protein and disrupts its function.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While pediatric NPH is less likely to be mentioned explicitly in the more recent literature, some of the articles published in the last decade have provided novel mechanistic insights into potential genetic and circulatory pathophysiology present in children, as well as in adults, which may contribute to the development of NPH across ages. Two pediatric articles have implicated genes pertinent to ependymal ciliary structure and function; coupled with a third recent study by Yang et al (2021) which observed a separate genetic defect also related to ependymal cilia function in 8/53 (15%) of adult idiopathic NPH patients who underwent full exosome DNA sequencing, this relatively new line of research provides insight into a potential mechanism of NPH related to cerebrospinal fluid production and circulation dynamics [ 1 , 3 , 32 ]. Separately, literature demonstrating altered cerebral blood flow dynamics in NPH supports one possible venous compensatory mechanism which may lead to ventricular dilation [ 2 , 4 , 5 , 28 ].…”
Section: Discussionmentioning
confidence: 99%